The Effect Of Celebrity Endorser And Brand Image Toward Purchase Decision - Rahayu, Aura; Anggraeni, Dewi; Hamdani, Nizar Alam; Herlianti, Anggun Oktavia (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
Purchasing decisions play a very important role because they can increase company profits through marketed products. Low purchasing decisions will be an obstacle with a low percentage of market share. The purpose of the study is to understand the celebrity endorser and brand image toward purchase decision as marketing phenomenon. The population of this study was Indonesian society, at least users of Emina moisturizing products aged 15-25. The survey was sent via online and face to face 747 randomly, there by individuals had the send probability of being selected from the population and the representing as sample. The data analysis technique in this quantitative study utilized a statistical approach. The program used to analyze the data with the regression method was static product and service solution (SPSS) to meet the criteria for data analysis using regression, an interval scale was utilized. The technique of analyzing the data in this study was regression. The data obtained in this study is accurate and reliable with a significance level of 95%. Based on the results of research on the analysis of celebrity endorsers influenced by brand image through purchase decision. Celebrity endorsers and brand image are important to increase sales and consumer loyalty, as well as attract new consumers.